Organizational learning culture and work engagement: the serial mediation effects of competencies and job crafting - Iman, Muhammad Faidhil; Salendu, Alice; Qotrunnada, Rifdah (Talenta Publisher, 2025)
Organizational learning culture (OLC) refers to a set of norms that facilitate continuous learning across all levels of the organization. OLC is believed to enhance employee work engagement, but it remains an area that requires further investigation due to its complexity and the varying impacts it may have. The relationship mechanism can be explained by increasing employee competencies in organizations with a learning culture. As competencies improve, they expand individual resources, enabling employees to craft their jobs with personal needs. Adopting the Conservation of Resources theory, researchers propose a resource caravan principle where employees are more likely to engage in organizations with a learning culture. Using a sample of 206 Indonesian employees, the data were analyzed using covariance-based structural equation modelling (CB-SEM). The results indicate a serial mediation effect, confirming the sequential influence of culture on work engagement. These findings offer insights for organizations to adopt a culture aligned with their goals and for researchers to understand the sequential mechanisms driven by a learning culture.